Effect of Aloe vera Gel as a Natural Antioxidant on the Quality of Cold-Stored Sea Bass (Dicentrarchus labrax) - Waris, Fachruqi; Pilavtepe-Celik, Mutlu (Mdpi, 2025)
Growing health and environmental concerns have intensified the search for natural antioxidants to replace synthetic alternatives to prevent spoilage of seafood. Long-term intake of synthetic antioxidants has been linked to liver toxicity, reproductive issues, and cancer risks in animals. This study therefore evaluates the efficacy of Aloe vera gel (AVG) as a natural antioxidant in preserving the quality of sea bass (Dicentrarchus labrax, Linnaeus 1758) slices during cold storage at 4 +/- 1 degrees C for 13 days. Sea bass slices were coated with 100% and 75% AVG and analyzed for physical (color and texture), chemical (pH, TVB-N, TBARS, and PV), and sensory changes. Results showed that AVG significantly reduced lipid oxidation, as indicated by lower peroxide (PV) and thiobarbituric acid reactive substances (TBARS) values in treated samples compared to controls. While sensory, color, and texture parameters remained consistent across all groups, 75% AVG-coated slices extended the shelf life by four days, and the 100% AVG treatment achieved a two-day extension, based on TVB-N values. These findings highlight AVG's potential as a natural, eco-friendly alternative to synthetic antioxidants for aquatic product preservation.
Keywords: Aloe vera; natural antioxidant; sea bass; lipid oxidation; cold storage; shelf life